2017
DOI: 10.1155/2017/4180490
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli in the Urine Samples of Iranian Dogs: Antimicrobial Resistance Pattern and Distribution of Antibiotic Resistance Genes

Abstract: Resistant uropathogenic Escherichia coli is the most common cause of urinary tract infections in dogs. The present research was done to study the prevalence rate and antimicrobial resistance properties of UPEC strains isolated from healthy dogs and those which suffered from UTIs. Four-hundred and fifty urine samples were collected and cultured. E. coli-positive strains were subjected to disk diffusion and PCR methods. Two-hundred out of 450 urine samples (44.4%) were positive for E. coli. Prevalence of E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…The most common determinant in the healthy isolates was the tet A gene ( n = 19), while tet B was detected in five isolates. These results are comparable with others described by Costa et al, Torkan et al and Yousefi et al [ 50 , 51 , 52 ]. On the other hand, the isolates from dogs with diarrhea showed a higher prevalence of the tet B gene ( n = 13) versus tet A ( n = 5).…”
Section: Resultssupporting
confidence: 93%
“…The most common determinant in the healthy isolates was the tet A gene ( n = 19), while tet B was detected in five isolates. These results are comparable with others described by Costa et al, Torkan et al and Yousefi et al [ 50 , 51 , 52 ]. On the other hand, the isolates from dogs with diarrhea showed a higher prevalence of the tet B gene ( n = 13) versus tet A ( n = 5).…”
Section: Resultssupporting
confidence: 93%
“…This study was conducted to evaluate the effectiveness of the combination treatment of imipenem and amikacin as an example of beta-lactam and aminoglycoside antibiotics in the treatment of multidrug-resistant (MDR) E. coli using checkerboard, time-kill curve studies techniques, and in vivo studies. Our analysis showed that E. coli was the most common species (40%), which agreed with many studies [ 41 , 42 ]. A study by Giacobbe, et al [ 43 ] showed that Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , and Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 92%
“…In Iran, E. coli strains producing blaSHV were isolated from raw milk and dairy products across the country (Ranjbar et al, 2018). Furthermore, this same gene was detected in Uropathogenic E. coli strains isolated from dogs (Yousefi and Torkan, 2017).…”
Section: Distribution Of Multi-drug Resistant Organisms In Animalsmentioning
confidence: 78%